Programa de autopsias virtuales o “virtuopsias” en el Hospital Clínico Universidad de Chile. Un importante eslabón para la generación de nuevo conocimiento y mejoramiento continuo. - Gómez M., Patricia; Zúñiga G., María Elena (Revista Hospital Clínico Universidad de Chile, 2019)
Most of today´s medical knowledge of current advances in medicine are based on autopsy findings and patological studies conducted during the 19th century. At the end of the 60s, autopsies began to decline in many countries, for multivariate reasons. Nowadays, autopsies are almost no longer performed unless legal reasons are present. The so important and didactic Pathological Anatomy Meetings are not being held anymore either. These instances played a particularly important role, bringing together and gathering experts and apprentices from different medical areas and disciplines. Unfortunately they have been disappearing from hospitals. However, physicians still seem to need them, as many times there is urgent need to get reliable information about the etiology of thepatients’ symptoms and the ultimate causes that led him or her to death. The relevance of this information for generating new knowledge and proposing new diagnostic or therapeutic tools for continuous improvement, both in the field of healthcare and training is indisputable. Unfortunately, we still face situations in which a patient dies in the midst of many doubts regarding the ultimate cause of death. At the University of Chile Clinical Hospital, a so-called Adverse Event Meetings have been held every Thursday for several years. A lot of time is spent trying to elucidate what could have happened, in an attempt to detect errors that could have been corrected A team of doctors, midwives and nurses, analyze all the adverse events reported, step by step. In spite of this, there are situations where doubts still persist, once the meeting is over. Currents advances in imaging, immune-histochemistry, molecular and genetic study techniques can make possible today to obtain most important information without the need for a traditional autopsy. These technologies, appear then as a substitute for traditional autopsies, since the realization of some of these post-mortem studies would allow to elucidate many diagnostic doubts, improving diagnostic.